2022
DOI: 10.1088/1475-7516/2022/12/008
|View full text |Cite
|
Sign up to set email alerts
|

Superradiance in stars: non-equilibrium approach to damping of fields in stellar media

Abstract: Superradiance in black holes is well-understood but a general treatment for superradiance in stars has until now been lacking. This is surprising given the ease with which we can observe isolated neutron stars and the array of signatures which would result from stellar superradiance. In this work, we present the first systematic pipeline for computing superradiance rates in rotating stars. Our method can be used with any Lagrangian describing the interaction between the superradiant field and the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Additionally, the process is effective when m is of the order of the black hole radius 1/(2GM ), and therefore, for fixed M , is active for larger boson masses (by a factor 2π/v dm ) than those for which DM capture starts to be effective, ξ foc ≃ 1. 31 Similar processes can occur in dense stellar objects like neutron stars, but require additional SM couplings beyond gravity and are not relevant for less dense objects like our Sun [142]. Finally, the particles produced by the Sun that lie in the low-velocity tail of the distribution can get captured into bound orbits around the Sun, giving rise to yet-another bound configuration, a solar basin [124,125,143].…”
Section: Jcap12(2023)021mentioning
confidence: 97%
“…Additionally, the process is effective when m is of the order of the black hole radius 1/(2GM ), and therefore, for fixed M , is active for larger boson masses (by a factor 2π/v dm ) than those for which DM capture starts to be effective, ξ foc ≃ 1. 31 Similar processes can occur in dense stellar objects like neutron stars, but require additional SM couplings beyond gravity and are not relevant for less dense objects like our Sun [142]. Finally, the particles produced by the Sun that lie in the low-velocity tail of the distribution can get captured into bound orbits around the Sun, giving rise to yet-another bound configuration, a solar basin [124,125,143].…”
Section: Jcap12(2023)021mentioning
confidence: 97%
“…Superradiance requires dissipation which in rotating BHs is provided by their ergoregion,7 but does not exist in neutron stars. Recent works have proposed that enough dissipation may come from finite conductivity either in the stellar magnetosphere [419,420] or within the star itself [421,422], but one may wonder if the required conditions can be met in realistic pulsars. More work may be needed to substantiate this exciting possibility.…”
Section: Pos(cosmicwispers)041mentioning
confidence: 99%
“…Superradiance in rotating stars has recently been discussed in refs. [67][68][69][70][71]. Reviews about superradiance can be found in refs.…”
Section: Introductionmentioning
confidence: 99%